2022
DOI: 10.3390/polym14214468
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Chemical Functionalization, and Commercial Applications of Nanocellulose and Nanocellulose-Based Composites: A Review

Abstract: Nanocellulose is the most abundant material extracted from plants, animals, and bacteria. Nanocellulose is a cellulosic material with nano-scale dimensions and exists in the form of cellulose nanocrystals (CNC), bacterial nanocellulose (BNC), and nano-fibrillated cellulose (NFC). Owing to its high surface area, non-toxic nature, good mechanical properties, low thermal expansion, and high biodegradability, it is obtaining high attraction in the fields of electronics, paper making, packaging, and filtration, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 157 publications
0
16
0
Order By: Relevance
“…The C6 primary hydroxyl groups were converted to carboxylate groups via NaClO/NaBr/TEMPO oxidation at three different TEMPO and NaBr catalyst levels [ 5 ]. This was measured via conductometric titration based on the consumed amounts of NaOH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C6 primary hydroxyl groups were converted to carboxylate groups via NaClO/NaBr/TEMPO oxidation at three different TEMPO and NaBr catalyst levels [ 5 ]. This was measured via conductometric titration based on the consumed amounts of NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…A FE-SEM (field emission scanning electron microscopy) was used to investigate the uniformity of fibril layers and any morphological changes upon the different degrees of oxidation and GO loadings. According to several studies, it has been found that surface modification via TEMPO does not influence the morphology of any TOCN samples [ 5 ]. Even with the introduction of the high amount of carboxylate groups, the original cellulose structure tends to be sustained since the oxidation preferably occurs on the surfaces and amorphous disordered regions [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this, various nanocellulose and cellulose derivatives have been developed by using a variety of methods such as mechanical, chemical, and biological methods. For example, Tahir et al 81 summarized the types, extraction methods, and possible chemical treatments that can enhance the properties of nanocellulose and its composites. Jiang and Ngai 82 summarized the structural and biochemical properties of cellulose and its derivatives.…”
Section: Characteristics and Classification Of Cellulosementioning
confidence: 99%
“…Compared with the mechanical method, the chemical method is better because it produces CNCs with improved crystallinity and reduces energy consumption [ 54 ]. However, acid hydrolysis is the most widely explored technique [ 55 , 56 ].…”
Section: Preparation Of Nanocellulosementioning
confidence: 99%